Pragmatic Communication Challenges in Children with Developmental Language Disorder: A Clinical-Pragmatic Case Study - Astri Widyaruli Anggraeni; Ruaidah Ruaidah; Fitri Amilia; Agus Milu Susetyo (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2025)
Developmental Language Disorder (DLD) is a prevalent yet underrecognized neurodevelopmental condition that affects children's expressive and receptive language skills. This study explores pragmatic communication difficulties in children with DLD using a clinical-pragmatic framework to inform assessment and intervention. A qualitative case study was conducted with three children aged 6 to 8 years diagnosed with DLD. Data were gathered through naturalistic observations, semi-structured interviews with caregivers and therapists, and video recordings of classroom and playtime interactions. Analysis followed Cummings’ clinical pragmatics model, focusing on speech acts, turn-taking, topic coherence, contextual relevance, and responses to indirect communication. Findings indicate a dominance of directive speech acts, reduced narrative coherence, delayed turn-taking, and limited understanding of indirect speech. Children frequently relied on nonverbal cues such as gestures and prosody to support meaning. The study highlights the need for multimodal interventions that integrate structural language development with pragmatic training. These findings offer implications for clinicians, educators, and researchers in designing ecologically valid, socially responsive interventions for children with DLD.